2019
DOI: 10.1002/bjs.11066
|View full text |Cite
|
Sign up to set email alerts
|

Growing research in global surgery with an eye towards equity

Abstract: Background Global surgery research is often generated through collaborative partnerships between researchers from both low‐ and middle‐income countries (LMICs) and high‐income countries (HICs). Inequitable engagement of LMIC collaborators can limit the impact of the research. Methods This article describes evidence of inequities in the conduct of global surgery research and outlines reasons why the inequities in this research field may be more acute than in other global health research disciplines. The paper g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Taken together, these advantages give HIC partners a greater chance at prime authorship along with more control over the nature of the collaboration; yet there are several ways to equalise the playing field. HIC researchers and their institutions could create more opportunities for local collaborators to contribute in ways that lead to prime authorship 24. Further, there are calls for HIC researchers to invest in the individual and institutional capacity building of their partners,25 including investments in skills that promote their leadership of research endeavours 26.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these advantages give HIC partners a greater chance at prime authorship along with more control over the nature of the collaboration; yet there are several ways to equalise the playing field. HIC researchers and their institutions could create more opportunities for local collaborators to contribute in ways that lead to prime authorship 24. Further, there are calls for HIC researchers to invest in the individual and institutional capacity building of their partners,25 including investments in skills that promote their leadership of research endeavours 26.…”
Section: Discussionmentioning
confidence: 99%
“…Although HIC-LMIC partnerships may open doors for some LIC/LMIC researchers, many other related factors may stifle the academic advancement of LIC/LMIC-based scientists. Traditional "North-South" institutional collaborations may have unbalanced and inequitable power dynamics that marginalize local scientists for myriad reasons [17]. Similarly, medical journals can hinder the progress of these collaborations by, for example, limiting LIC/ LMIC editorial board representation, which may lead to inadequate understanding of LIC/LMIC-based research in the context of the material and human resource limitations that often exists in these environments [17].…”
Section: Discussionmentioning
confidence: 99%
“…Such sentiments echo the oftentimes lopsided nature of collaborative work that has been described in opinion pieces previously. 12,14,16 Furthermore, a large proportion of respondents reported that HIC investigators had set the agenda for research conducted in LMICs. This finding aligns with comments published 20 years ago in the BMJ and echoed again in a more recent policy piece on inclusivity in global health published in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Global health research has been called a "field of power relations" because of the imbalances in influence between LMIC and HIC investigators. 10 Some academicians have argued that the popular shift in terminology from collaboration to "partnership" [11][12][13] may simply reflect "postcolonial anxieties" among HIC collaborators. 14 Partnerships between LMIC and HIC investigators are sometimes paternalistic, and academic global health collaborations may unequally benefit HIC investigators when compared with LMIC investigators.…”
Section: Introductionmentioning
confidence: 99%